Mengasah Potensi Melalui Kegiatan Olimpiade Anak Hebat - Dewi Sekar Arum; Maytita Tri Hardiyanti; Muhammad Nabil Akmal; Didit Darmawan; Busro Muhammad Al Mursyidi; Rahayu Mardikaningsih; Derisma Vita Noviyanti; Febriarsita Eka Sasmita (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This article examines the value of children's involvement in the Great Children's Olympics as a means to develop their potential. Through entertaining and educational competitions, the Olympics aims to improve children's social, cognitive and motor skills. Through the use of a PAR approach, the researcher was able to gain first-hand insight into the needs and development of the children during the Olympics, as well as actively engage participants in the research process and provide opportunities for them to contribute to the development of this activity. By using this technique, the researcher was able to adapt the program in real time in response to feedback from participants and observers, making the program more inclusive and sensitive to the needs of each individual. The PAR method was used in the Great Kids Olympics, and the results are highlighted in this article. The results showed that the children who participated in this activity not only significantly improved their intelligence, social skills, and self-confidence, but also developed a sense of responsibility and cooperation. The research also emphasizes the importance of involving parents, teachers and facilitators among other stakeholders in creating activities that can maximize children's potential. The article argues that by using a PAR approach in activities such as the Great Children's Olympics, children's potential can be developed holistically and more meaningful and sustainable learning can be facilitated.